The association between diffusion-weighted imaging-Alberta Stroke Program Early Computed Tomography Score and the outcome following mechanical thrombectomy of anterior circulation occlusion - Hiroaki Hashimoto; Tomoyuki Maruo; Yuki Kimoto; Masami Nakamura; Takahiro Fujinaga; Hajime Nakamura; Yukitaka Ushio (Interdisciplinary Neurosurgery, 2023)
Background: Although preoperative diffusion-weighted imaging-Alberta Stroke Program Early Computed Tomography Score (DWI-ASPECTS) is well known as a predictor of outcomes after mechanical thrombectomy (MT) for large-vessel occlusion (LVO), assessment of changes in DWI-ASPECT from before to after MT is rare. Therefore, we clarified the relationship between the change in DWI-ASPECTS and clinical outcomes. Methods: In this retrospective single-center study, we enrolled 63 cases of anterior LVOs treated with MT between April 2015 and March 2022. Preoperative and postoperative DWI-ASPECTSs were calculated. DWI-ASPECTSs were categorized into cortical-ASPECTSs (c-ASPECTSs) and subcortical ASPECTSs and assessed. Additionally, medical variables related to patients, such as sex, age, National Institutes of Health Stroke Scale (NIHSS) score, and premorbid modified Rankin Scale (mRS) score, were evaluated. A good outcome was defined as an mRS score of 0–2 at 3 months. Results: Forty-five patients met the inclusion criteria. Nine (20 %) had a good outcome. The good outcome group showed significantly higher postoperative DWI-ASPECTs (median 8 vs. 5, p = 0.012) and c-ASPECTSs (median 4 vs. 3, p = 0.020) than the poor outcome group. No difference in DWI-ASPECTSs and c-ASPECTSs from before to after MT were significantly associated with the good outcome (p = 0.017, p = 0.016, respectively). The cut-off values for the good outcome on receiver operating characteristic curve analysis for differences between DWI-ASPECTSs and c-ASPECTSs were 0 [area under the curve (AUC) 0.77] and 0 [AUC 0.74]. Logistic regression analyses showed that baseline NIHSS score (odds ratio, 0.69; 95 % confidence interval 0.48–1.00; p = 0.046) and postoperative DWI-ASPECTS (odds ratio, 2.27; 95 % confidence interval 1.02–5.04; p = 0.039) were independent factors for the good outcome. Conclusions: The good outcome of patients with anterior LVO was associated with no difference in DWI-ASPECTSs and c-ASPECTSs from before to after MT.